Students' Perception of English Learning through YouTube Application - Jessy Gracella; Dedi Rahman Nur (Borneo Educational Journal (Borju), 2020)
As one of the most popular social media in this modern era, YouTube is also playing a role in education. Technology, which is part of student life, can offer useful feedback, especially in facilitating, increasing knowledge and English skills. An audio-visual model that can be accessed anywhere can make students feel more open about thoughts, opinions, questions, and be more comfortable and motivated in learning English. This article reports a qualitative study that finds out students' perceptions of English learning through YouTube are beneficial and help them learn English. 5 students who use the YouTube application as a media for learning English in SMK Negeri 17 participated in this study, and data were collected through interview-based on case study design. The results of this study find out all of the students have many benefits to improve their English skills, and very easy to access in almost every student's gadget and it can be used in every situation for help and motivated them to learn English. The students are only feeling the difficulty if the internet connection is not good. All of the students are given positive responses about the use of YouTube application in learning English.